(3GdeYQV GdSfhj GdYGe GdKGef h GdYTQjf (B2009- (3LeYjI GdGeGQGJ ddafhf GdJTcjdjIs : The 28th Annual Fine Arts Exhibition - Abdulaziz, Ebtisam- (3GHJSGe YHO GdYRjRs; AlRefa'i, Ismail- (3ESeGYjd GdQaGYjs; Aydabi, Mohammad AlWaddah- (3eMeO GdhVGM jhSa YjOGHjs; Hamilton, Ayesha; (3LeYjI GdEeGQGJ ddafhf GdJTcjdjIs; EFAS (Sharjah; Dept. of Culture and Information, Govt of Sharjah; Emirates Fine Arts Society; Dept. of Culture and Info, Govt. of Sharjah, 2009)
Exhibition catalog. Curator: Ebtisam Abdulaziz. Contributors: Ismail AlRifa'i, Aisha Hamilton, Mohammad AlWaddah Y. Aydabi.
English; Arabic
Keywords: N4390-5098 Visual Arts. Exhibitions; UAE